Does depression treatment improve the survival of depressed patients with cancer? A long-term follow-up of participants in the SMaRT Oncology-2 and 3 trials. (April 2018) - Mulick, Amy; Walker, Jane; Puntis, Stephen; Burke, Katy; Symeonides, Stefan; Gourley, Charlie; Wanat, Marta; Frost, Chris; Sharpe, Michael
Summary: Background: Comorbid major depression has been associated with worse survival in patients with cancer. However, we do not know if treating depression improves survival. In the SMaRT Oncology-2 (good prognosis cancers) and SMaRT Oncology-3 (lung cancer, a poor prognosis cancer) trials, we found that a depression treatment programme, Depression Care for People with Cancer (DCPC), was effective in reducing comorbid major depression. In this analysis, we aimed to identify whether DCPC also had an effect on survival. Methods: The trials were conducted in three cancer centres and their associated clinics in Scotland, UK. In SMaRT Oncology-2, outpatients with good prognosis cancers and major depression were randomly assigned in a 1:1 ratio to DCPC or usual care, with stratification (by trial centre) and minimisation (by age, primary cancer, and sex) with allocation concealment. In SMaRT Oncology-3, outpatients with lung cancer and major depression were randomly assigned (1:1 ratio) to DCPC or usual care with stratification (by trial centre) and minimisation (by age, sex, and cancer type) with allocation concealment. For this analysis, we obtained long-term data on deaths (all causes) in the SMaRT Oncology-2 and 3 trial participants, censored at July 31, 2015, and analysed survival as a trial outcome. We estimated unadjusted hazard ratios (HRs) for each trial using Cox regression, and pooled the log HRs in a fixed-effects meta-analysis. Findings: We recruited 642 participants; between May 12, 2008, and May 13, 2011, 500 participants were recruited to the SMaRT Oncology-2 trial and between Jan 5, 2009, and Sept 9, 2011, 142 participants were recruited to the SMaRT Oncology-3 trial. We followed up SMaRT Oncology-2 and SMaRT Oncology-3 participants for a median of 5 years and 1 year, respectively. 135 (27%) of 500 SMaRT Oncology-2 participants and 114 (80%) of 142 SMaRT Oncology-3 participants died within this period. We found no significant effect of DCPC on survival in the total follow-up period for either SMaRT Oncology 2 (HR 1·02, 95% CI 0·72–1·42, p=0·93) or SMaRT Oncology-3 (HR 0·82, 95% CI 0·56–1·18, p=0·28; pooled HR 0·92, 95% CI 0·72–1·18, p=0·51). Interpretation: DCPC is highly effective in improving depression and quality of life in depressed patients with cancer, but there was no evidence for a significant effect on survival. Despite the absence of an effect on length of life, the management of depression remains important for its beneficial effect on quality of life. Funding: NIHR CLAHRC Oxford, Cancer Research UK, and the Chief Scientist Office of the Scottish Government.